2011
DOI: 10.1164/rccm.201008-1249oc
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Structure and Body Fat Composition in Obese Children with Obstructive Sleep Apnea Syndrome

Abstract: Rationale: Mechanisms leading to obstructive sleep apnea syndrome (OSAS) in obese children are not well understood. Objectives: The aim of the study was to determine anatomical risk factors associated with OSAS in obese children as compared with obese control subjects without OSAS. Methods: Magnetic resonance imaging was used to determine the size of upper airway structure, and body fat composition. Paired analysis was used to compare between groups. Mixed effects regression models and conditional multiple log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 40 publications
3
95
0
4
Order By: Relevance
“…12,15,32 In adolescents, visceral adiposity is associated with OSA risk in some, 32 although not all studies, 33 and enlarged neck circumference has been associated with increased upper airway collapsibility. 34 Recursive partitioning identified those with the highest BMI (> 99th percentile) as being a distinct sub-population.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,32 In adolescents, visceral adiposity is associated with OSA risk in some, 32 although not all studies, 33 and enlarged neck circumference has been associated with increased upper airway collapsibility. 34 Recursive partitioning identified those with the highest BMI (> 99th percentile) as being a distinct sub-population.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 OSAS is frequently associated with benign adenotonsillar hypertrophy, but other possible causes such as the anatomy of the craniofacial anomalies, abnormal neuromuscular tone and respiratory disorders have also been reported. 2 A crucial factor in the genesis of OSAS is the increase in the soft-tissue volume. The speed of growth of the skeleton surrounding the upper airway is in fact lower than that of the characteristic soft tissues, in particular the lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no correlation shown between the severity of OSAS and variation in body fat distribution. The same study identified an increase in tonsil volume in OSAS cases (10). In this study for the first time the correlation between tonsil volume measured with TCU in obese adolescents with hepatosteatosis was assessed and the tonsil volume was revealed to be higher in obese cases with hepatosteatosis.…”
Section: Discussionmentioning
confidence: 53%
“…In recent times studies have determined that transcervical ultrasound (TCU) is a practical method to measure the size of the palatine tonsils (8,9). Additionally, in the recent period there are studies evaluating the correlation of upper respiratory tract stenosis in obese children with OSAS and lymphoid tissue size and fat distribution in abdominal organs with MRI (10). To the best of our knowledge, there is no sonographic study assessing the correlation between fat accumulation in abdominal organs and tonsil size in the literature.The aim of this study is the measure the size of the palatine tonsils in adolescents with TCU and research the correlation with body mass index (BMI) and hepatosteatosis.…”
Section: Introductionmentioning
confidence: 99%